Hereditary polyposis coli. III. Genetic and evolutionary fitness. - Murphy, E A (1980)
The numbers of progeny born to 355 patients with heritable polyposis of the colon and to 315 related, but normal, subjects, all old enough to have completed their families, are presented, as well as data on 432 subjects still young enough to have more children. Two main indices are used: mean family size ("genetic fitness") and the complement of the extinction probability of the line ("evolutionary fitness"), both of which suppose a steady state. Point- and interval-estimates (the latter derived by an extension of Stigler's method) are furnished. It is estimated that the probability a new mutant gene will persist is one in four for Gardner syndrome, one in 20 for familial polyposis coli, and 0 for Peutz-Jeghers syndrome. There is evidence of bimodality in family size, suggesting voluntary infertility in a proportion of subjects. The data confirm our provisional working assumption that most families are completed by the time women are in their mid-40's and men in their mid-50's.